3D Robot Vision System through 2D Shape Based Matching Using Gaussian Smoothing for Gluing Application - Haniff Harun, Mohamad; Shahrieel Mohd Aras, Mohd; Firdaus Mohd Ab Halim, Mohd; Azha Mohd Annuar, Khalil; Hadi Azahar, Arman; Faizal Yaakub, Muhamad; Faiz Zainal Abidin, Amar (International Journal of Engineering and Technology, 2018)
This investigation is solely on the adaptation of a vision system algorithm to classify the processes to regulate the decision making related to the tasks and defectâ€™s recognition. These idea stresses on the new method on vision algorithm which is focusing on the shape matching properties to classify defects occur on the product. The problem faced before that the system required to process broad data acquired from the object caused the time and efficiency slightly decrease. The propose defect detection approach combine with Region of Interest, Gaussian smoothing, Correlation and Template Matching are introduced. This application provides high computational savings and results in better recognition rate about 95.14%. The defects occur provides with information of the height which corresponds by the z-coordinate, length which corresponds by the y-coordinate and width which corresponds by the x-coordinate. This data gathered from the proposed system using dual camera for executing the three dimensional transformation.Â Â